2017
DOI: 10.1136/archdischild-2017-313454
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of thyrotoxicosis in childhood and adolescence in the west of Scotland: the case for long-term antithyroid treatment and the importance of initial counselling

Abstract: BackgroundThyrotoxicosis is both rarer and more severe in children than in adults, rendering management difficult and often unsatisfactory.ObjectiveTo ascertain outcome in a geographically defined area of Scotland between 1989 and 2014.MethodRetrospective case note review with follow-up questionnaire to family doctors for patients with Graves’ disease and Hashimoto’s thyroiditis.ResultsSixty-six patients (58 females:8 males) comprising 53 with Graves’ disease and 13 with Hashimoto’s thyroiditis were diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 26 publications
2
23
1
6
Order By: Relevance
“…The second frequent cause of juvenile thyrotoxicosis is hashitoxicosis and its prevalence was reported as 0.5% to 22% in different studies (9). Like as results reported in a recent study from Scotland and 19.6% of patients with thyrotoxicosis classified as hashitoxicosis in that cohort (20). The distinction of GD and hashitoxicosis may be difficult as seen in this study, the most common reported presenting complaints among patients with GD and hashitoxicosis are similar.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The second frequent cause of juvenile thyrotoxicosis is hashitoxicosis and its prevalence was reported as 0.5% to 22% in different studies (9). Like as results reported in a recent study from Scotland and 19.6% of patients with thyrotoxicosis classified as hashitoxicosis in that cohort (20). The distinction of GD and hashitoxicosis may be difficult as seen in this study, the most common reported presenting complaints among patients with GD and hashitoxicosis are similar.…”
Section: Resultssupporting
confidence: 78%
“…Very few studies continue in this respect and some completed studies have shown conflicting results (11)(12)(13). Remission is reported approximately in one third of children with GD and subsequently relapse occurs in half of patients after achieved remission (7,(14)(15)(16)(17)(18)(19)(20)(21). Remission rates are lower and relapse rates are higher in children than in adults (22).…”
Section: Introductionsmentioning
confidence: 99%
“…This proportion is slightly higher than the proportion (43%) found in a recent Scottish study [35]. In that study, radioactive iodine treatment was given much more frequently than in our study.…”
Section: Discussioncontrasting
confidence: 54%
“…Some clinicians believe that hypothyroidism is preferable to hyperthyroidism, because it is easier to treat and has a less serious morbidity [29]. However, medical adherence is problematic not only for long-term ATD therapy but also for the thyroxine supplement after hypothyroidism induced by definite therapy [30, 31]. Further long-term, prospective studies are required to determine the optimal duration of ATD treatment for pediatric GD.…”
Section: Discussionmentioning
confidence: 99%